Ghee based nanostructured lipid carriers (NLCs) with improved wound-healing effects: Ghee based nanostructured lipid carriers (NLCs) - Haji, Mohammad; Hosseinzadeh, Marzieh; Jahangiri, Yaghoub; Farajzadeh, Zahra; Mostashari Sufiani, Asra; Alipour Olyaei, Yousef; Barzegarzadeh Namarvar, Behnaz; Ghaffari, Tayyebeh; Alipour Olyaei, Nasrin (Iranian Journal of Pharmaceutical Sciences, 2023)
Ghee or butter oil is an excellent medium for preparing herbal cosmetics and Ayurvedic medicines formulations. However, water immiscibility restrict its use as a potential carrier system in particular in lipid-based topical formulations. In this work, we prepared ghee-based nanostructured lipid carriers (NLCs) using olive oil as liquid lipid, Tween 60 as surfactant and glycerol as co-surfactant by hot emulsification–ultrasonication method. Then the loaded NLC with a mixture of ethanolic extracts of Achillea millefolium, Horsetail and Plantago major L. was prepared in the same way. NLCs were characterized in terms of size, zeta potential, polydispersity index (PDI) and creaming index. The particle size of NLCs was lower than 100 nm and the zeta potential displayed the negative charge in all formulations. The results of creaming index showed that NLCs were stable for up to 8 weeks under refrigerated conditions. The wound healing effects of the NLCs were evaluated using an excision model in rats. The NLCs displayed significant increased wound contraction and decreased epithelialization period when compare to standard drug phenytoin. This study showed that the ghee-based formulations are much more efficacious in NLC for wound healing promotion in comparison with their macroemulsion form. The formulated system is easy to produce and to apply and could be favourable for topical application in pharmaceutical industries.